Resveratrol-induced gut microbiota reduces obesity in high-fat diet-fed mice - Wang, Pan; Li, Daotong; Ke, Weixin; Liang, Dong; Hu, Xiaosong; Chen, Fang (International Journal of Obesity, 2020)
Resveratrol (RSV) is a natural polyphenol with putative anti-obesity effects; however, its mechanisms of action remain unclear due to its low bioavailability. Microbial functions in the physiology result from the microbiota-host coevolution has profoundly affected host metabolism. Here, we sought to determine how beneficial microbiome caused by RSV interventions affects antiobesity. C57BL/6J mice were fed either standard diet (SD) or RSV (300 mg/kg/day) diet for 16 weeks. The composition of the gut microbiota was assessed by analyzing 16S rRNA gene sequences. Then, transplant the RSV-microbiota to high-fat diet (HFD)-fed mice (HFD-RSVT) to explore the function of microbiota. Body weight and food intake were monitored. Markers of lipid metabolism, inflammation, gut microbiota compostion, and intestinal barrier were determined. Mice treated with RSV shows a remarkable alteration in microbiota composition compared with that of SD-fed mice and is characterized by an enrichment of Bacteroides, Lachnospiraceae_NK4A136_group, Blautia, Lachnoclostridium, Parabacteroides, and Ruminiclostridium_9, collectively referred to as RSV-microbiota. We further explored whether RSV-microbiota has anti-obesity functions. Transplantation of the RSV-microbiota to high-fat diet (HFD)-fed mice (HFD-RSVT) was sufficient to decrease their weight gain and increase their insulin sensitivity. Moreover, RSV-microbiota was able to modulate lipid metabolism, stimulate the development of beige adipocytes in WAT, reduce inflammation and improve intestinal barrier function. Our study demonstrates that RSV-induced microbiota plays a key role in controlling obesity development and brings new insights to a potential therapy based on host-microbe interactions.